Lithium supplementing method, pre-lithiated negative pole piece, secondary battery and electronic device

By forming a prelithiated layer and a dense SEI film on the negative electrode sheet of the lithium-ion battery, the shortcomings of the lithium-ion battery in terms of first-time Coulomb efficiency and cycle life are solved, and a higher energy density and a simplified preparation process are achieved.

CN119920844AActive Publication Date: 2025-05-02NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510111746.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The negative active materials of existing lithium-ion batteries, silicon carbon and silicon oxygen materials, have insufficient first-time Coulomb efficiency and cycle life, resulting in energy density not meeting the demand.

Method used

A lithium supplement method is adopted to form a prelithiated layer on the negative electrode sheet, and a dense and stable solid electrolyte interface film (SEI film) is formed by discharging treatment to supplement the active lithium lost during the charge and discharge process and improve the transmission efficiency of lithium ions.

Benefits of technology

The first Coulomb efficiency of the secondary battery is improved, the cycle capacity attenuation is reduced, the energy density is improved, and the battery preparation process is simplified, the production efficiency is improved and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920844A_ABST
    Figure CN119920844A_ABST
Patent Text Reader

Abstract

The invention provides a lithium supplementing method, a pre-lithiated negative pole piece, a secondary battery and an electronic device. The lithium supplementing method of the negative pole piece comprises the following steps: providing the negative pole piece and a lithium supplementing composite layer; the lithium supplementing composite layer and the negative pole piece are attached, the lithium supplementing composite layer and the negative pole piece are subjected to discharging treatment, the discharging treatment is divided into a first stage, a second stage and a third stage according to the time sequence, and the discharging currents and the discharging time of all the stages are different; after the discharging treatment is finished, stripping the lithium supplementing composite layer from the negative pole piece to obtain a first pre-lithiated negative pole piece; and storing the first pre-lithiated negative pole piece to obtain a second pre-lithiated negative pole piece. When the second pre-lithiated negative pole piece prepared by the lithium supplementing method is applied to the secondary battery, the first coulombic efficiency and the energy density of the secondary battery can be improved, and the cycle capacity attenuation is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a lithium supplementation method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device. Background Art

[0002] Secondary batteries, such as lithium-ion batteries, have the advantages of high energy density, high power, and long cycle life. They are widely used in consumer electronics, electric bicycles, and electric vehicles. As their application scope continues to expand, the energy density and cycle performance requirements of lithium-ion batteries continue to increase. The current common lithium-ion battery negative electrode active material graphite can no longer meet the requirements for energy density. Although silicon-carbon and silicon-oxygen negative electrode active materials have high theoretical specific capacity, they are ideal materials to replace negative electrode active materials graphite and improve the energy density of lithium-ion batteries. However, they have not been widely used due to their low first coulomb efficiency and poor cycle life. The existing method to improve the first coulomb efficiency and reduce the cycle capacity attenuation of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrode active materials is to pre-replenish lithium to the negative electrode plate to supplement the irreversible capacity consumed in the first charge, discharge, and cycle, improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrode active materials, and then improve the energy density of lithium-ion batteries.

[0003] The existing methods of replenishing lithium in negative electrode sheets mainly include replenishing lithium with lithium powder, replenishing lithium with lithium strips, and replenishing lithium with electrochemical methods. However, the above three methods of replenishing lithium have certain problems in environmental control, uniformity of replenishing lithium, and side reactions after replenishing lithium. Therefore, it is urgent to provide a method of replenishing lithium in negative electrode sheets to improve the first coulombic efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrode active materials, reduce cycle capacity attenuation, and improve the energy density of lithium-ion batteries. Summary of the invention

[0004] The purpose of this application is to provide a lithium replenishment method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device to improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity decay, and improve the energy density of the secondary battery. The specific technical solution is as follows:

[0005] The first aspect of the present application provides a method for replenishing lithium of a negative electrode plate, which comprises the following steps:

[0006] (1) A negative electrode sheet is provided, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector.

[0007] (2) Providing a lithium supplement composite layer, the lithium supplement composite layer comprising a support layer, a lithium supplement layer and a separator pre-impregnated with an electrolyte, wherein the lithium supplement layer is disposed between the separator pre-impregnated with an electrolyte and the support layer.

[0008] (3) The lithium replenishing composite layer and the negative electrode plate are laminated so that the isolation film pre-impregnated with the electrolyte contacts the negative electrode material layer, and the lithium replenishing composite layer and the negative electrode plate are discharged. The discharge treatment is divided into a first stage, a second stage and a third stage in chronological order. The constant current discharge current of the first stage is 0.1C to 0.3C, and the discharge time is 0.008h to 0.28h. The constant current discharge current of the second stage is 1C to 2C, and the discharge time is 0.032h to 0.30h. The constant current discharge current of the third stage is 0.3C to 0.5C, and the discharge time is 0.027h to 0.058h.

[0009] (4) After the discharge treatment is completed, the lithium supplement composite layer is peeled off from the negative electrode plate to obtain a first pre-lithiated negative electrode plate.

[0010] (5) The first pre-lithiated negative electrode sheet is stored in an environment of 20° C. to 30° C. and humidity ≤1.7% for 12 h to 72 h to obtain a second pre-lithiated negative electrode sheet.

[0011] The lithium replenishment method of the present application is used to replenish the negative electrode plate with lithium, which can replenish the active lithium lost during the first charge and discharge process of the secondary battery due to the formation of the solid electrolyte interface film (SEI film) and the active lithium lost during the cycle process, and by adjusting the conditions of the discharge treatment, the first stage discharge can achieve the formation of a dense inorganic SEI film, the second stage discharge can achieve the formation of a loose organic SEI film, and shorten the lithium replenishment time, improve the lithium replenishment efficiency, and the third stage discharge can achieve the integrity and stability of the SEI film, thereby forming a dense SEI film on the surface of the negative electrode plate. The lithium replenishment method of the present application and the electrolyte of the present application in the isolation membrane pre-impregnated with the electrolyte can also improve the stability of the SEI film on the surface of the negative electrode plate in the environment, which is more conducive to the formation of a dense and stable SEI film on the surface of the negative electrode plate, and improve the stability and integrity of the SEI film. At the same time, since a dense and stable SEI film has been formed during the above-mentioned discharge treatment and storage treatment, the formation step can be omitted in the subsequent preparation process of the secondary battery. Therefore, the second pre-lithiation negative electrode plate prepared by the lithium replenishment method of the present application can improve the environmental stability of the negative electrode plate. Applying it to a secondary battery can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. It can also simplify the preparation process of the secondary battery, improve production efficiency, and reduce preparation costs.

[0012] In some embodiments of the present application, the first coulombic efficiency of the first pre-lithiated negative electrode plate applied to the secondary battery is the first first coulombic efficiency E1, the first coulombic efficiency of the second pre-lithiated negative electrode plate applied to the secondary battery is the second first coulombic efficiency E2, 90%≤E2 / E1≤100%. When the value of E2 / E1 is within the above range, the secondary battery has a higher first coulombic efficiency, a lower cycle capacity attenuation, and a higher energy density.

[0013] In some embodiments of the present application, 90%≤E1≤120%. When the value of E1 is within the above range, the secondary battery has a higher first coulombic efficiency, a lower cycle capacity decay, and a higher energy density.

[0014] In some embodiments of the present application, the coverage of lithium fluoride on the surface of the first pre-lithiated negative electrode plate is 45% to 85%, and the coverage of lithium fluoride on the surface of the second pre-lithiated negative electrode plate is 45% to 95%. When the coverage of lithium fluoride on the surface of the first pre-lithiated negative electrode plate and the second pre-lithiated negative electrode plate is within the above range, the SEI film on the surface of the negative electrode plate has high integrity and stability, and the ionic conductivity is also high, and the secondary battery has a high first coulomb efficiency, a low cycle capacity attenuation, and a high energy density.

[0015] In some embodiments of the present application, the mass content of hydrogen fluoride on the surface of the first pre-lithiated negative electrode plate is 10ppm to 450ppm, and the mass content of hydrogen fluoride on the surface of the second pre-lithiated negative electrode plate is 10ppm to 500ppm. The mass content of hydrogen fluoride on the surface of the first pre-lithiated negative electrode plate and the second pre-lithiated negative electrode plate is within the above range, indicating that the negative electrode plate has fewer side reactions during the discharge treatment lithium replenishment process and the storage process, the integrity of the SEI film on the surface of the negative electrode plate is high, and the secondary battery has a higher first coulomb efficiency, lower cycle capacity attenuation and higher energy density.

[0016] In some embodiments of the present application, the electrolyte includes an additive, the additive includes a non-fluorine additive, the non-fluorine additive includes at least one of lithium hexamethyldisilazide, lithium thiodicarbonate or lithium bis(oxalatoborate); based on the mass of the electrolyte, the mass percentage of the non-fluorine additive is 0.1% to 10%. The electrolyte includes the above-mentioned non-fluorine additive, and its mass percentage is regulated within the above-mentioned range, which is conducive to forming a stable SEI film on the surface of the negative electrode plate, improving the stability of the SEI film on the surface of the negative electrode plate, and improving the environmental stability of the negative electrode plate when placed in an air environment for a long time, thereby helping to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0017] In some embodiments of the present application, the electrolyte includes an additive, the additive includes a fluorine-containing additive, and the fluorine-containing additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium fluorosulfonyl(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium (trifluoromethyl)(nonafluorobutyl)sulfonylimide, or lithium 1,3-perfluoropropanedisulfonylimide; based on the mass of the electrolyte, the mass percentage of the fluorine-containing additive is 0% to 5%. The electrolyte includes the above-mentioned fluorine-containing additive, and the mass percentage thereof is regulated within the above-mentioned range, which is beneficial to improving the hydrolysis resistance of the electrolyte and improving the stability of the SEI film on the surface of the negative electrode sheet, thereby facilitating improving the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0018] In some embodiments of the present application, the electrolyte includes a non-aqueous organic solvent, and the non-aqueous organic solvent includes ethylene carbonate; based on the mass of the electrolyte, the mass percentage of ethylene carbonate is 32.5% to 91%. The electrolyte includes ethylene carbonate, and its mass percentage is regulated within the above range, which is conducive to dissolving lithium salts, improving the ionic conductivity of the electrolyte, and also conducive to forming a stable SEI film on the surface of the negative electrode plate, improving the stability of the SEI film on the surface of the negative electrode plate, and improving the environmental stability of the negative electrode plate when placed in an air environment for a long time, thereby facilitating the improvement of the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0019] In some embodiments of the present application, the temperature of the discharge treatment is 25° C. to 90° C. By regulating the temperature of the discharge treatment within the above range, it is beneficial to shorten the lithium replenishment time, improve the lithium replenishment efficiency, and achieve a good lithium replenishment effect, thereby facilitating the improvement of the first coulombic efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0020] In some embodiments of the present application, the interface pressure per unit area between the lithium replenishing composite layer and the negative electrode piece is 0.1MPa to 0.6MPa. By regulating the interface pressure per unit area between the lithium replenishing composite layer and the negative electrode piece within the above range, the distance between the lithium replenishing composite layer and the negative electrode piece can be shortened, the impedance of lithium ion transmission in the lithium replenishing composite layer and the negative electrode piece can be reduced, the lithium replenishing time can be shortened, and the lithium replenishing efficiency can be improved, which is conducive to improving the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0021] In some embodiments of the present application, the surface density of the electrolyte on the separator pre-impregnated with the electrolyte is 3 g / mm 2 Up to 60g / mm 2By regulating the surface density of the electrolyte on the separator pre-impregnated with the electrolyte within the above range, it is beneficial to increase the transmission rate of lithium ions in the lithium replenishment composite layer and the negative electrode material layer, thereby improving the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and increasing the energy density of the secondary battery.

[0022] In some embodiments of the present application, the surface density of the electrolyte on the separator pre-impregnated with the electrolyte is 5 g / mm 2 Up to 30g / mm 2 By regulating the surface density of the electrolyte on the separator pre-impregnated with the electrolyte within the above range, it is beneficial to further improve the transmission rate of lithium ions in the lithium replenishment composite layer and the negative electrode material layer, thereby further improving the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0023] The second aspect of the present application provides a pre-lithiated negative electrode plate prepared according to the lithium supplementation method in any of the aforementioned embodiments. The pre-lithiated negative electrode plate of the present application is applied to a secondary battery, which can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. It can also simplify the preparation process of the secondary battery, improve production efficiency, and reduce preparation costs.

[0024] The third aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. The secondary battery of the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.

[0025] The fourth aspect of the present application provides an electronic device, which comprises the secondary battery in any of the above embodiments. The electronic device of the present application has a long service life and good performance.

[0026] Beneficial effects of this application:

[0027] The present application provides a lithium replenishment method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device. The lithium replenishment method can replenish the active lithium lost by the formation of a solid electrolyte interface film (SEI film) during the first charge and discharge process of the secondary battery and the active lithium lost during the cycle process, and by adjusting the conditions of the discharge treatment, the first stage discharge can realize the formation of a dense inorganic SEI film, the second stage discharge can realize the formation of a loose organic SEI film, and shorten the lithium replenishment time, improve the lithium replenishment efficiency, and the third stage discharge can realize the integrity and stability of the SEI film, thereby forming a dense SEI film on the surface of the negative electrode plate. The lithium replenishment method of the present application and the electrolyte of the present application in the isolation film pre-impregnated with the electrolyte can also improve the stability of the SEI film on the surface of the negative electrode plate in the environment, which is more conducive to the formation of a dense and stable SEI film on the surface of the negative electrode plate, and improve the stability and integrity of the SEI film. At the same time, since a dense and stable SEI film has been formed during the above-mentioned discharge treatment and storage treatment, the formation step can be omitted in the subsequent preparation process of the secondary battery. Therefore, the second pre-lithiation negative electrode plate prepared by the lithium replenishment method of the present application can improve the environmental stability of the negative electrode plate. Applying it to a secondary battery can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. It can also simplify the preparation process of the secondary battery, improve production efficiency, and reduce preparation costs.

[0028] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0030] Figure 1 This is a schematic diagram of the structure of the negative electrode plate during the lithium replenishment process according to an implementation scheme of the present application.

[0031] Reference numerals: negative electrode plate 110 , negative electrode current collector 111 , negative electrode material layer 112 , lithium supplement composite layer 120 , separator 121 pre-impregnated with electrolyte, lithium supplement layer 122 , support layer 123 . DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0033] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0034] The first aspect of the present application provides a method for replenishing lithium of a negative electrode plate, which comprises the following steps:

[0035] (1) A negative electrode sheet is provided, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector.

[0036] (2) Providing a lithium supplement composite layer, the lithium supplement composite layer comprising a support layer, a lithium supplement layer and a separator pre-impregnated with an electrolyte, wherein the lithium supplement layer is disposed between the separator pre-impregnated with an electrolyte and the support layer.

[0037] (3) The lithium replenishing composite layer and the negative electrode plate are laminated so that the isolation film pre-impregnated with the electrolyte contacts the negative electrode material layer, and the lithium replenishing composite layer and the negative electrode plate are discharged. The discharge treatment is divided into a first stage, a second stage and a third stage in chronological order. The constant current discharge current of the first stage is 0.1C to 0.3C, and the discharge time is 0.008h to 0.28h. The constant current discharge current of the second stage is 1C to 2C, and the discharge time is 0.032h to 0.30h. The constant current discharge current of the third stage is 0.3C to 0.5C, and the discharge time is 0.027h to 0.058h.

[0038] Exemplarily, the constant current discharge current of the first stage can be 0.1C, 0.12C, 0.15C, 0.18C, 0.2C, 0.23C, 0.25C, 0.28C, 0.3C, or a range consisting of any two of the above values, and the discharge time can be 0.008h, 0.03h, 0.05h, 0.07h, 0.1h, 0.13h, 0.15h, 0.18h, 0.20h, 0.22h, 0.25h, 0.28h, or a range consisting of any two of the above values; the constant current discharge current of the second stage can be 1C, 1.1C, 1.2C, 1.3C, 1.4C, 1.5C, 1.6C, 1.7C, 1.8C, 1.9C, 2C, or a range consisting of any two of the above values. The discharge time can be 0.032h, 0.05h, 0.07h, 0.1h, 0.13h, 0.15h, 0.18h, 0.20h, 0.22h, 0.25h, 0.28h, 0.30h or a range consisting of any two of the above values; the constant current discharge current in the third stage can be 0.3C, 0.34C, 0.38C, 0.4C, 0.43C, 0.45C, 0.48C, 0.5C or a range consisting of any two of the above values, and the discharge time can be 0.027h, 0.030h, 0.035h, 0.040h, 0.042h, 0.045h, 0.048h, 0.052h, 0.058h or a range consisting of any two of the above values.

[0039] (4) After the discharge treatment is completed, the lithium supplement composite layer is peeled off from the negative electrode plate to obtain a first pre-lithiated negative electrode plate.

[0040] (5) The first pre-lithiated negative electrode sheet is stored in an environment of 20° C. to 30° C. and humidity ≤1.7% for 12 h to 72 h to obtain a second pre-lithiated negative electrode sheet.

[0041] Exemplarily, the storage temperature of the first pre-lithiated negative electrode plate can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C or a range consisting of any two of the above values, the humidity can be 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.7% or a range consisting of any two of the above values, and the time can be 12h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 72h or a range consisting of any two of the above values.

[0042] The lithium replenishment method of the present application is used to replenish lithium for the negative electrode plate. The lithium replenishment layer and the negative electrode material layer can form an external short circuit. The lithium atoms in the lithium replenishment layer undergo an oxidation reaction to lose electrons to generate lithium ions. The lithium ions are transmitted to the surface or the inside of the negative electrode material layer through the isolation membrane pre-impregnated with electrolyte. The electrons are transmitted to the negative electrode current collector through an external circuit and then to the surface or the inside of the negative electrode material layer. The electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form lithium-embedded compounds, thereby achieving pre-lithiation of the negative electrode material layer to replenish the active lithium lost due to the formation of the SEI film during the first charge and discharge process and the active lithium lost during the cycle process.

[0043] Since an isolation membrane pre-impregnated with electrolyte is arranged between the lithium replenishment layer and the negative electrode material layer, the above-mentioned isolation membrane has good ion conductivity, which can reduce the probability of the lithium replenishment layer adhering to the surface of the negative electrode material layer, reduce the influence of side reactions that may occur in the negative electrode material layer due to the high activity of lithium metal in the lithium replenishment layer on the electrochemical performance of the secondary battery, and can also reduce the influence of the silicone oil residue on the surface of the lithium replenishment layer entering the surface of the negative electrode material layer on the electrochemical performance of the secondary battery.

[0044] The lithium replenishment composite layer and the negative electrode plate are subjected to discharge treatment, and the conditions of the discharge treatment are adjusted within the scope of this application. The first stage of discharge treatment can realize the formation of a dense inorganic SEI film, the second stage of discharge treatment can realize the formation of a loose organic SEI film, and shorten the lithium replenishment time and improve the lithium replenishment efficiency. The third stage of discharge treatment can realize the integrity and stability of the SEI film, thereby forming a dense SEI film on the surface of the negative electrode plate, reducing the probability of the negative electrode active material being destroyed due to the co-embedding of solvent molecules, improving the transmission efficiency of lithium ions, and reducing the side reactions between the negative electrode plate and the electrolyte. After the discharge treatment is completed, the lithium replenishment composite layer is peeled off from the negative electrode plate to obtain the first pre-lithiated negative electrode plate. The above-mentioned stripping process can reduce the impact of the side reactions that occur after the lithium metal single substance in the lithium replenishment layer remains on the surface of the negative electrode material layer and enters the secondary battery on the electrochemical performance of the secondary battery.

[0045] However, the SEI film formed on the surface of the first pre-lithiated negative electrode piece after the discharge treatment has poor stability when placed in an air environment for a long time, and is easily reacted with CO2 and H2O to form inorganic lithium salts such as Li2CO3 and Li2O. At the same time, the lithium in the SEI film will also react with O2 to form various strongly nucleophilic oxides, and react with organic molecules and semi-carbonates to form carbonates and alcohol salts. The use of the lithium replenishment method of the present application and the use of the electrolyte of the present application in the isolation membrane pre-impregnated with the electrolyte can improve the stability of the SEI film on the surface of the negative electrode piece in the air environment, and is more conducive to the formation of a dense and stable SEI film on the surface of the negative electrode piece, thereby improving the stability and integrity of the SEI film. At the same time, since a dense and stable SEI film has been formed during the above-mentioned discharge treatment and storage treatment process, the formation step can be omitted in the subsequent preparation process of the secondary battery, reducing the consumption of the electrolyte during the formation process and increasing the overall electrolyte retention in the secondary battery.

[0046] When the constant current discharge current of the first stage discharge treatment is too small, for example, less than 0.1C, the inorganic SEI film formed is too dense, which is not conducive to the transmission of lithium ions, and the dynamics of the secondary battery is poor; when the constant current discharge current of the first stage discharge treatment is too large, for example, greater than 0.3C, the inorganic SEI film formed is too loose, although it is conducive to the transmission of lithium ions, but the stability of the SEI film is poor. When the discharge time of the first stage discharge treatment is too small, for example, less than 0.008h, the thickness of the inorganic SEI film formed is too thin, and the stability of the SEI film is poor; when the discharge time of the first stage discharge treatment is too large, for example, greater than 0.28h, the thickness of the inorganic SEI film formed is too thick, which is not conducive to the transmission of lithium ions, and the dynamics of the secondary battery is poor. When the constant current discharge current of the second stage discharge treatment is too small, for example, less than 1C, the organic SEI film formed is too dense, which is not conducive to the transmission of lithium ions, and the dynamics of the secondary battery is poor; when the constant current discharge current of the second stage discharge treatment is too large, for example, greater than 2C, the organic SEI film formed is too loose, and the stability of the SEI film is poor. When the discharge time of the second stage discharge treatment is too small, for example, less than 0.032h, the thickness of the organic SEI film formed is too thin, and the stability of the SEI film is poor; when the discharge time of the second stage discharge treatment is too large, for example, greater than 0.30h, the thickness of the organic SEI film formed is too thick, which is not conducive to the transmission of lithium ions, and the dynamics of the secondary battery is poor. When the constant current discharge current of the third stage discharge treatment is too small, for example, less than 0.3C, the SEI film formed is too dense, and the dynamics of the secondary battery is poor; when the constant current discharge current of the third stage discharge treatment is too large, for example, greater than 0.5C, the SEI film formed is too loose, and its integrity and stability are poor. When the discharge time of the third stage discharge treatment is too small, for example, less than 0.027h, the thickness of the SEI film formed is too thin, and its integrity and stability are poor; when the discharge time of the third stage discharge treatment is too large, for example, greater than 0.058h, the thickness of the SEI film formed is too thick, and the dynamics of the secondary battery is poor.

[0047] When the storage temperature of the first pre-lithiated negative electrode sheet is too low, for example, below 20°C, although the degree of side reactions of the obtained second pre-lithiated negative electrode sheet is reduced, the cost of storage and processing of the negative electrode sheet increases, and practical application is difficult; when the storage temperature of the first pre-lithiated negative electrode sheet is too high, for example, above 30°C, the SEI film formed on the surface of the negative electrode sheet is prone to side reactions, resulting in poor compactness and stability of the SEI film. When the humidity during storage of the first pre-lithiated negative electrode sheet is too high, for example, greater than 1.7%, the SEI film formed on the surface of the negative electrode sheet is prone to side reactions, resulting in poor compactness and stability of the SEI film. When the storage time of the first pre-lithiated negative electrode is too short, for example, less than 12 hours, although the degree of side reactions in the obtained second pre-lithiated negative electrode is reduced, the production is difficult to achieve, that is, it is difficult to prepare a secondary battery in a short time after the negative electrode is replenished with lithium; when the storage time of the first pre-lithiated negative electrode is too long, for example, more than 72 hours, the SEI film formed on the surface of the negative electrode is prone to side reactions, resulting in poor compactness and stability of the SEI film. Therefore, any of the constant current discharge current and discharge time of the first, second, and third stage discharge treatments, as well as any of the temperature, humidity, and time of the storage treatment are not within the scope of this application, and will affect the first coulomb efficiency, cycle performance, and energy density of the secondary battery, or the process is difficult to achieve.

[0048] Therefore, the second pre-lithiation negative electrode plate prepared by the lithium replenishment method of the present application can improve the environmental stability of the negative electrode plate. Applying it to a secondary battery can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. It can also simplify the preparation process of the secondary battery, improve production efficiency, and reduce preparation costs.

[0049] In the present application, the water content of the negative electrode plate in step (1) is ≤500ppm. The negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved. It can be understood that the above-mentioned negative electrode plate refers to a negative electrode plate that has not been pre-lithiated.

[0050] In some embodiments of the present application, the electrolyte includes an additive, the additive includes a non-fluorine additive, and the non-fluorine additive includes at least one of lithium hexamethyldisilazide (LiHMDS), lithium thiodicarbonate (LiTDI) or lithium bis(oxalatoborate) (LiBOB); based on the mass of the electrolyte, the mass percentage of the non-fluorine additive is 0.1% to 10%. Exemplarily, the mass percentage of the non-fluorine additive can be 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the above values. The electrolyte includes the above-mentioned non-fluorine additive, and its mass percentage is regulated within the above range, which is conducive to forming a stable SEI film on the surface of the negative electrode, improving the stability of the SEI film on the surface of the negative electrode, improving the environmental stability of the negative electrode when it is placed in an air environment for a long time, and improving the integrity of the SEI film, thereby helping to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0051] In some embodiments of the present application, the electrolyte includes an additive, the additive includes a fluorine-containing additive, and the fluorine-containing additive includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium fluorosulfonyl (trifluoromethylsulfonyl)imide (LiFTFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiBETi), lithium (trifluoromethyl) (nonafluorobutyl) sulfonyl imide, or lithium 1,3-perfluoropropanedisulfonyl imide; based on the mass of the electrolyte, the mass percentage of the fluorine-containing additive is 0% to 5%. Exemplarily, the mass percentage of the fluorine-containing additive can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any two of the above values. The electrolyte includes the above-mentioned fluorine-containing additive, and its mass percentage is regulated within the above-mentioned range, which is beneficial to improving the hydrolysis resistance of the electrolyte, reducing the side reaction between the residual electrolyte in the negative electrode material layer and the moisture in the environment during storage, improving the stability of the SEI film on the surface of the negative electrode plate, improving the environmental stability of the negative electrode plate when placed in an air environment for a long time, and improving the integrity of the SEI film, which is beneficial to improving the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0052] In some embodiments of the present application, the electrolyte includes a non-aqueous organic solvent, and the non-aqueous organic solvent includes ethylene carbonate (EC); based on the mass of the electrolyte, the mass percentage of ethylene carbonate is 32.5% to 91%. Exemplarily, the mass percentage of ethylene carbonate can be 32.5%, 40%, 50%, 60%, 70%, 80%, 91% or a range consisting of any two of the above values. The electrolyte includes ethylene carbonate, and regulating its mass percentage within the above range is conducive to dissolving lithium salts, improving the ionic conductivity of the electrolyte, and also conducive to forming a stable SEI film on the surface of the negative electrode plate, improving the stability of the SEI film on the surface of the negative electrode plate, improving the environmental stability of the negative electrode plate when placed in an air environment for a long time, and improving the integrity of the SEI film, thereby helping to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0053] In some embodiments, the electrolyte also includes other non-aqueous organic solvents, and the mass percentage of other non-aqueous organic solvents is 0% to 50% based on the mass of the electrolyte. Exemplarily, the mass percentage of other non-aqueous organic solvents can be 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or the range of any two of the above numerical values. The present application is not particularly limited to the types of other non-aqueous organic solvents, as long as the purpose of the present application can be achieved. For example, other non-aqueous organic solvents can include at least one of carbonate compounds, carboxylate compounds, ether compounds or other electrolyte organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorocarbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of vinylene carbonate, propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to at least one of fluorinated ethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The other electrolyte organic solvents may include but are not limited to at least one of 1,3-propane sultone, dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate.

[0054] In some embodiments, the electrolyte further comprises a lithium salt, and the mass percentage of the lithium salt is 8% to 20% based on the mass of the electrolyte. Exemplarily, the mass percentage of the lithium salt can be 8%, 10%, 12%, 13%, 14%, 16%, 18%, 20% or a range consisting of any two of the above values. The present application does not particularly limit the type of lithium salt, and lithium salts known in the art can be used. Exemplarily, the lithium salt can include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), bistrifluoromethanesulfonyl imide lithium (LiN (CF3SO2) 2, LiTFSI), bis (fluorosulfonyl) imide lithium (Li (N (SO2F) 2), LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis oxalate borate (LiB (C2O4) 2, LiBOB) or lithium difluoro oxalate borate (LiBF2 (C2O4), LiDFOB).

[0055] In some embodiments, the expansion rate of the separator in the lithium-supplement composite layer after being soaked in the electrolyte at 25°C to 90°C for 24 hours is 1% to 10%. Exemplarily, the expansion rate of the separator in the lithium-supplement composite layer after being soaked in the electrolyte at 25°C to 90°C for 24 hours can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the above values. The expansion rate of the separator in the lithium-supplement composite layer after being soaked in the electrolyte at 25°C to 90°C for 24 hours is within the above range, and the distance of lithium ions transmitted from the lithium-supplement layer to the negative electrode material layer is within a preferred range, which is conducive to reducing the impedance of lithium ions transmitted in the lithium-supplement composite layer and the negative electrode sheet, shortening the lithium-supplement time, and improving the lithium-supplement efficiency, thereby helping to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. In this application, the expansion rate refers to the volume expansion rate.

[0056] The present application does not particularly limit the method of regulating the expansion rate of the separator after soaking in the electrolyte, as long as the purpose of the present application can be achieved. For example, at least one surface of the separator substrate layer of the present application may be provided with a coating containing a polymer, and the expansion rate of the separator after soaking in the electrolyte can be regulated by regulating the type or particle size of the polymer in the separator coating and the coating amount of the separator coating. Generally, when other conditions remain unchanged, the greater the expansion rate of the polymer in the coating, the greater the expansion rate of the separator after soaking in the electrolyte; the smaller the expansion rate of the polymer in the coating, the smaller the expansion rate of the separator after soaking in the electrolyte. When other conditions remain unchanged, the larger the particle size of the polymer in the coating, the greater the expansion rate of the separator after soaking in the electrolyte; the smaller the particle size of the polymer in the coating, the smaller the expansion rate of the separator after soaking in the electrolyte. When other conditions remain unchanged, the coating amount of the coating increases, the expansion rate of the separator after soaking in the electrolyte increases; the coating amount of the coating decreases, and the expansion rate of the separator after soaking in the electrolyte decreases. The type of separator and the composition ratio of the electrolyte usually also affect the expansion rate of the separator after soaking in the electrolyte.

[0057] In some embodiments of the present application, the surface density of the electrolyte on the separator pre-impregnated with the electrolyte is 3 g / mm 2 Up to 60g / mm 2 Preferably, the surface density of the electrolyte on the separator pre-impregnated with electrolyte is 5 g / mm 2 Up to 30g / mm 2 For example, the surface density of the electrolyte on the separator pre-impregnated with the electrolyte may be 3 g / mm 2 , 5g / mm 2 , 10g / mm 2 , 15g / mm 2 , 20g / mm 2 , 25g / mm 2 、30g / mm 2 , 40g / mm 2 , 50g / mm 2 、60g / mm 2 Or a range consisting of any two of the above values. By regulating the surface density of the electrolyte on the separator pre-impregnated with the electrolyte within the above range, the separator contains an appropriate amount of electrolyte, which can reduce the risk of the electrolyte entering the negative electrode material layer and the uncontrollable lithium replenishment process due to excessive electrolyte content, improve the operability of the lithium replenishment process, and at the same time help to increase the transmission rate of lithium ions in the lithium replenishment composite layer and the negative electrode material layer, increase the amount of lithium replenishment in the negative electrode material layer, and improve the integrity and stability of the SEI film, which is conducive to improving the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0058] The present application does not particularly limit the method of regulating the surface density of the electrolyte on the separator pre-impregnated with electrolyte, as long as the purpose of the present application can be achieved. For example, the surface density of the electrolyte on the separator pre-impregnated with electrolyte can be regulated by regulating the amount of electrolyte dripped or sprayed on the surface of the separator and the immersion time of the separator in the electrolyte. Generally, when other conditions remain unchanged, the amount of electrolyte dripped or sprayed on the surface of the separator increases, and the surface density of the electrolyte on the separator pre-impregnated with electrolyte increases; the amount of electrolyte dripped or sprayed on the surface of the separator decreases, and the surface density of the electrolyte on the separator pre-impregnated with electrolyte decreases. When other conditions remain unchanged, the immersion time of the separator in the electrolyte increases, and the surface density of the electrolyte on the separator pre-impregnated with electrolyte increases; the immersion time of the separator in the electrolyte decreases, and the surface density of the electrolyte on the separator pre-impregnated with electrolyte decreases. The type of separator and the composition ratio of the electrolyte usually also affect the surface density of the electrolyte on the separator pre-impregnated with the electrolyte.

[0059] In some embodiments, the elongation of the isolation membrane under a tensile force of 2N / 10mm to 4N / 10mm is 0% to 1%. For example, the elongation of the isolation membrane under a tensile force of 2N / 10mm to 4N / 10mm can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of the above values. The isolation membrane that meets the above characteristics has high mechanical strength and is not prone to breakage during the lithium replenishment process, which is conducive to improving the efficiency of lithium replenishment.

[0060] In some embodiments, the tensile strength of the separator in the running (MD) direction is 4000 kg / cm 2 Up to 7000kg / cm 2 , the tensile strength in the direction perpendicular to the tape (TD) is 2000kg / cm 2 Up to 4000kg / cm 2 The MD direction is the length direction of the separator, and the TD direction is the width direction of the separator. For example, the tensile strength of the separator in the MD direction can be 4000 kg / cm 2 , 4500kg / cm 2 , 5000kg / cm 2 、5500kg / cm 2 、6000kg / cm 2 、6500kg / cm 2 , 7000kg / cm 2 Or a range consisting of any two of the above values; the tensile strength of the isolation film in the direction perpendicular to the tape run (TD) can be 2000kg / cm 2 , 2500kg / cm 2、3000kg / cm 2 、3500kg / cm 2 , 4000kg / cm 2 Or it is a range consisting of any two of the above values. The isolation membrane that meets the above characteristics has high mechanical strength and is not prone to breakage during the lithium replenishment process, which is beneficial to improving the lithium replenishment efficiency.

[0061] The separator of the present application can be reused as long as the separator is not damaged after the lithium replenishment is completed. For example, the separator can be reused more than 5 times. The first coulombic efficiency of the second pre-lithiated negative electrode sheet prepared by the separator for the first time is a1, and the first coulombic efficiency of the second pre-lithiated negative electrode sheet prepared by the separator for the i-th time (1≤i≤15) is a i , a i / a1 is 99% to 100%, indicating that the reused isolation membrane has little effect on the first coulombic efficiency of the secondary battery and can be maintained at a high level, which is beneficial to reducing the cost of the preparation process.

[0062] The present application has no particular restrictions on the thickness of the isolation membrane, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation membrane can be 3μm to 30μm. The present application has no particular restrictions on the material of the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0063] In some embodiments, the lithium supplement layer includes at least one of lithium foil or lithium alloy foil, and the material of the lithium alloy foil may include but is not limited to at least one of lithium aluminum alloy, lithium silicon alloy, lithium magnesium alloy, lithium tin alloy or lithium nickel alloy. Based on the mass of the lithium supplement layer, the mass percentage of lithium element in the lithium supplement layer may be 97% to 100%.

[0064] In some embodiments, the thickness of the lithium replenishment layer is 5 μm to 200 μm, preferably 10 μm to 100 μm. Exemplarily, the thickness of the lithium replenishment layer can be 5 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm or a range consisting of any two of the above values. By regulating the thickness of the lithium replenishment layer within the above range, the lithium replenishment layer can better meet the lithium replenishment demand while reducing the preparation cost, which is beneficial to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0065] In some embodiments, the tensile strength at break of the lithium supplement layer along the walking (MD) direction is 0.5N / 10mm to 200N / 10mm, preferably 1N / 10mm to 100N / 10mm. Exemplarily, the tensile strength at break of the lithium supplement layer along the walking (MD) direction can be 0.5N / 10mm, 1N / 10mm, 20N / 10mm, 50N / 10mm, 80N / 10mm, 100N / 10mm, 120N / 10mm, 150N / 10mm, 180N / 10mm, 200N / 10mm or a range consisting of any two of the above values. The tensile strength at break of the lithium supplement layer along the walking (MD) direction is within the above range, the lithium supplement layer has a high mechanical strength, is not prone to breakage during the lithium supplement process, and is conducive to achieving a good lithium supplement effect, thereby facilitating the improvement of the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery.

[0066] In some embodiments, the support layer includes at least one of a metal foil, a polyethylene terephthalate film, a polypropylene film or a polyethylene film, and the metal foil includes a copper foil, a nickel foil, a steel foil or a copper-nickel alloy foil. The above-mentioned support layer is selected, and the support layer can provide better support for the lithium replenishment layer and the isolation membrane pre-impregnated with the electrolyte, and improve the mechanical strength of the lithium replenishment composite layer, so that the lithium replenishment composite layer can be completely peeled off from the surface of the negative electrode material layer more smoothly after lithium replenishment, and the possibility of fracture of the lithium replenishment composite layer is reduced, which is beneficial to improve the lithium replenishment efficiency of the negative electrode sheet, thereby facilitating the improvement of the first coulomb efficiency of the secondary battery, reducing the cycle capacity attenuation, and improving the energy density of the secondary battery. The present application does not have any special restrictions on the thickness of the support layer, as long as the purpose of the present application can be achieved. For example, the thickness of the support layer can be 3μm to 50μm, and preferably, the thickness of the support layer can be 5μm to 20μm.

[0067] The present application has no particular restrictions on the preparation method of the lithium supplement layer, as long as the purpose of the present application can be achieved. For example, in some embodiments, a lithium metal powder slurry is applied to the support layer and dried and rolled to form a lithium supplement layer; in other embodiments, a lithium foil and / or a lithium alloy foil is rolled to the support layer to form a lithium supplement layer; in yet other embodiments, a lithium or lithium alloy molten slurry is applied to the support layer and cooled and rolled to form a lithium supplement layer. The present application has no particular restrictions on the roller pressure of the rolling process in the preparation of the above-mentioned lithium supplement layer, as long as the purpose of the present application can be achieved. For example, the roller pressure can be 0.1T / 10mm to 2T / 10mm.

[0068] In the present application, in step (3), the lithium supplement composite layer and the negative electrode plate are laminated so that the separator pre-impregnated with the electrolyte is in contact with the negative electrode material layer. Figure 1As shown, for ease of understanding, the thickness direction of the negative electrode sheet and the lithium supplement composite layer is defined as Y, the negative electrode sheet 110 includes a negative electrode current collector 111 and a negative electrode material layer 112 arranged on both surfaces of the negative electrode current collector 111, and the lithium supplement composite layer 120 includes a support layer 123, a lithium supplement layer 122 and an isolation film 121 pre-impregnated with an electrolyte, and the lithium supplement layer 122 is arranged between the isolation film 121 pre-impregnated with an electrolyte and the support layer 123. The lithium supplement composite layer 120 and the negative electrode sheet 110 are laminated so that the isolation film 121 pre-impregnated with an electrolyte is in contact with the negative electrode material layer 112. It can be understood that the above-mentioned negative electrode sheet refers to a negative electrode sheet that has not been pre-lithiated.

[0069] In the present application, the lithium replenishment composite layer and the negative electrode plate are discharged through a voltage control system, wherein the positive electrode of the voltage control system is connected to the negative electrode plate, and the negative electrode of the voltage control system is connected to the lithium replenishment layer. During the above-mentioned discharge treatment, the potential of the negative electrode plate is higher than that of the lithium replenishment layer. The negative electrode plate serves as the "positive electrode" and the lithium replenishment layer serves as the "negative electrode". Therefore, if the lithium replenishment of the negative electrode plate is to be achieved and the lithium ions are transferred from the lithium replenishment layer to the negative electrode plate, a discharge treatment is required.

[0070] In some embodiments of the present application, the temperature of the discharge treatment is 25°C to 90°C. Exemplarily, the temperature of the discharge treatment can be 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, 85°C, 90°C, or a range consisting of any two of the above values. During the discharge treatment, the lithium atoms in the lithium replenishment layer lose electrons to form lithium ions, and the lithium ions are transferred to the surface or the inside of the negative electrode material layer through the isolation membrane pre-impregnated with the electrolyte, and the electrons are transferred to the negative electrode current collector through the external circuit and then to the surface or the inside of the negative electrode material layer. By regulating the temperature of the discharge treatment within the above range, it is beneficial to increase the transmission speed of lithium ions in the lithium replenishment composite layer and the negative electrode material layer, shorten the lithium replenishment time, improve the lithium replenishment efficiency, and reduce the safety risks caused by excessive temperature during the lithium replenishment process. At the same time, it is beneficial to form a dense and stable SEI film on the surface of the negative electrode plate, and in the subsequent preparation process of the secondary battery, the formation step is omitted, the consumption of electrolyte in the formation process is reduced, and the overall electrolyte retention in the secondary battery is increased, which is beneficial to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and increase the energy density of the secondary battery. At the same time, it simplifies the preparation process of the secondary battery, improves production efficiency, and reduces preparation costs.

[0071] In some embodiments of the present application, the interface pressure per unit area between the lithium replenishing composite layer and the negative electrode piece is 0.1MPa to 0.6MPa. Exemplarily, the interface pressure per unit area between the lithium replenishing composite layer and the negative electrode piece can be 0.1MPa, 0.15MPa, 0.2MPa, 0.25MPa, 0.3MPa, 0.35MPa, 0.4MPa, 0.45MPa, 0.5MPa, 0.55MPa, 0.6MPa or a range consisting of any two of the above values. By regulating the interface pressure per unit area between the lithium replenishing composite layer and the negative electrode piece within the above range, the distance between the lithium replenishing composite layer and the negative electrode piece can be shortened, the impedance of lithium ion transmission in the lithium replenishing composite layer and the negative electrode piece can be reduced, the lithium replenishing time can be shortened, and the lithium replenishing efficiency can be improved, which is beneficial to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0072] The present application does not particularly limit the manner in which the lithium-replenishing composite layer and the negative electrode sheet are bonded, as long as the purpose of the present application can be achieved. For example, the manner in which the lithium-replenishing composite layer and the negative electrode sheet are bonded can be winding into a roll or pressing into a sheet. The present application does not particularly limit the method for regulating the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, when the lithium-replenishing composite layer and the negative electrode sheet are wound into a roll, the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode sheet can be regulated by regulating the winding tension. When other conditions remain unchanged, the winding tension increases, and the interface pressure per unit area increases; the winding tension decreases, and the interface pressure per unit area decreases. For example, when the lithium-replenishing composite layer and the negative electrode sheet are pressed into a sheet, the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode sheet can be regulated by regulating the pressing pressure. When other conditions remain unchanged, the pressing pressure increases, and the interface pressure per unit area increases; the pressing pressure decreases, and the interface pressure per unit area decreases.

[0073] In some embodiments, after the discharge treatment is completed, the peeling force between the separator of the pre-impregnated electrolyte and the lithium replenishing layer is 1N / m to 5N / m. Exemplarily, the peeling force between the separator of the pre-impregnated electrolyte and the lithium replenishing layer can be 1N / m, 1.5N / m, 2N / m, 2.5N / m, 3N / m, 3.5N / m, 4N / m, 4.5N / m, 5N / m or a range composed of any two of the above values. The peeling force between the separator of the pre-impregnated electrolyte and the lithium replenishing layer is within the above range. After the discharge treatment is completed, the separator is easier to separate from the lithium replenishing layer, which can reduce the probability of the lithium metal element in the lithium replenishing layer remaining on the surface of the negative electrode material layer, reduce the possibility of the lithium metal element having side reactions in the negative electrode material layer, and can also reduce the probability of the lithium replenishing layer remaining on the surface of the separator, increase the number of times the separator is used, reduce costs, and improve the surface lithium precipitation of the negative electrode material layer, thereby helping to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0074] In some embodiments, after the discharge treatment, the peeling force between the separator pre-impregnated with the electrolyte and the negative electrode material layer is 1N / m to 8N / m. Exemplarily, the peeling force between the separator pre-impregnated with the electrolyte and the negative electrode material layer can be 1N / m, 1.5N / m, 2N / m, 2.5N / m, 3N / m, 3.5N / m, 4N / m, 4.5N / m, 5N / m, 6N / m, 7N / m, 8N / m, or a range consisting of any two of the above values. The peeling force between the isolation membrane pre-impregnated with electrolyte and the negative electrode material layer is within the above range. After the discharge treatment is completed, the isolation membrane is easier to separate from the negative electrode material layer, which can reduce the probability of lithium metal in the lithium replenishment layer remaining on the surface of the negative electrode material layer, reduce the possibility of lithium metal having side reactions in the negative electrode material layer, and also reduce the probability of negative electrode active material remaining on the surface of the isolation membrane, increase the number of times the isolation membrane is used, reduce costs, and improve the surface lithium deposition of the negative electrode material layer, which is beneficial to improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.

[0075] In some embodiments of the present application, the first coulombic efficiency of the first pre-lithiated negative electrode plate applied to the secondary battery is the first first coulombic efficiency E1, and the first coulombic efficiency of the second pre-lithiated negative electrode plate applied to the secondary battery is the second first coulombic efficiency E2, 90% ≤ E2 / E1 ≤ 100%. Exemplarily, the value of E2 / E1 can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or a range consisting of any two of the above values. When the value of E2 / E1 is within the above range, during the storage process of the first pre-lithiated negative electrode plate, the side reaction between the residual electrolyte in the negative electrode material layer and the moisture in the environment is less, and the integrity and stability of the SEI film on the surface of the second pre-lithiated negative electrode plate obtained are better, which is conducive to improving the environmental stability of the negative electrode plate, so that the secondary battery has a higher first coulombic efficiency, lower cycle capacity attenuation and higher energy density.

[0076] In some embodiments of the present application, 90% ≤ E1 ≤ 120%. For example, the value of E1 can be 90%, 95%, 100%, 102%, 105%, 108%, 110%, 112%, 115%, 118%, 120%, or a range consisting of any two of the above values. When the value of E1 is within the above range, the secondary battery has a higher first coulombic efficiency, a lower cycle capacity decay, and a higher energy density.

[0077] In some embodiments, 81%≤E2≤120%. Exemplarily, the value of E2 can be 81%, 85%, 90%, 95%, 100%, 102%, 105%, 108%, 110%, 112%, 115%, 118%, 120%, or a range consisting of any two of the above values. When the value of E2 is within the above range, the secondary battery has a higher first coulombic efficiency, a lower cycle capacity decay, and a higher energy density.

[0078] In some embodiments of the present application, the coverage of lithium fluoride on the surface of the first pre-lithiated negative electrode plate is 45% to 85%, and the coverage of lithium fluoride on the surface of the second pre-lithiated negative electrode plate is 45% to 95%. Exemplarily, the coverage of lithium fluoride on the surface of the first pre-lithiated negative electrode plate can be 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or a range consisting of any two of the above values, and the coverage of lithium fluoride on the surface of the second pre-lithiated negative electrode plate can be 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or a range consisting of any two of the above values. The lithium fluoride on the surface of the negative electrode plate is usually generated during the lithium replenishment process and storage process of the negative electrode plate discharge treatment. The presence of lithium fluoride is beneficial to improve the mechanical strength, chemical stability and ionic conductivity of the SEI film and reduce the further decomposition reaction of the electrolyte and the SEI film. The coverage of lithium fluoride on the surface of the first pre-lithiated negative electrode plate and the second pre-lithiated negative electrode plate is within the above range, the SEI film integrity and stability on the surface of the negative electrode plate are high, and the ionic conductivity is also high, so that the secondary battery has a higher first coulombic efficiency, lower cycle capacity attenuation and higher energy density.

[0079] In some embodiments of the present application, the mass content of hydrogen fluoride on the surface of the first pre-lithiated negative electrode plate is 10ppm to 450ppm, and the mass content of hydrogen fluoride on the surface of the second pre-lithiated negative electrode plate is 10ppm to 500ppm. Exemplarily, the mass content of hydrogen fluoride on the surface of the first pre-lithiated negative electrode plate can be 10ppm, 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, or a range consisting of any two of the above values, and the mass content of hydrogen fluoride on the surface of the second pre-lithiated negative electrode plate can be 10ppm, 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, or a range consisting of any two of the above values. Hydrogen fluoride on the surface of the negative electrode plate is usually generated during the discharge treatment, lithium replenishment and storage process of the negative electrode plate. Hydrogen fluoride will corrode the SEI film, and its presence is not conducive to the stability of the SEI film. The mass content of hydrogen fluoride on the surface of the first pre-lithiated negative electrode plate and the second pre-lithiated negative electrode plate is within the above range, indicating that the negative electrode plate has fewer side reactions during the discharge treatment, lithium replenishment and storage process, has better environmental stability, and has a higher integrity of the SEI film on the surface of the negative electrode plate, so that the secondary battery has a higher first coulomb efficiency, lower cycle capacity decay and higher energy density.

[0080] The present application has no particular restrictions on the environmental parameters in steps (1) to (4), as long as the purpose of the present application can be achieved. For example, the environmental parameters of step (1) can be temperature ≤ 30°C and humidity ≤ 1.7%, the environmental parameters of step (2) can be temperature ≤ 30°C and humidity ≤ 1.7%, the environmental parameters of step (3) can be humidity ≤ 1.7%, and the environmental parameters of step (4) can be temperature ≤ 30°C and humidity ≤ 1.7%.

[0081] In some embodiments, the lithium replenishment of the negative electrode plate can be achieved by the following methods: (1) soaking the separator in the electrolyte to form a separator pre-impregnated with the electrolyte. (2) unwinding the support layer provided with the lithium replenishment layer, the separator pre-impregnated with the electrolyte, and the negative electrode plate, and then rolling them into a roll in the above order; or stacking the support layer provided with the lithium replenishment layer, the separator pre-impregnated with the electrolyte, and the negative electrode plate in sequence in the above order. (3) connecting the positive electrode of the voltage control system to the negative electrode plate, and connecting the negative electrode of the voltage control system to the lithium replenishment layer, and performing a discharge treatment on the lithium replenishment composite layer and the negative electrode plate, and the discharge treatment is divided into a first stage, a second stage, and a third stage in chronological order. (4) After the discharge treatment is completed, the support layer provided with the lithium replenishment layer, the separator pre-impregnated with the electrolyte, and the negative electrode plate are unwound and rolled up separately; or the support layer provided with the lithium replenishment layer, the separator pre-impregnated with the electrolyte, and the negative electrode plate are disassembled to obtain a first pre-lithiated negative electrode plate. (5) The first pre-lithiated negative electrode sheet is stored in an environment of 20° C. to 30° C. and humidity ≤1.7% for 12 h to 72 h to obtain a second pre-lithiated negative electrode sheet.

[0082] The second aspect of the present application provides a pre-lithiated negative electrode plate prepared according to the lithium replenishment method in any of the aforementioned embodiments. The above-mentioned pre-lithiated negative electrode plate refers to a second pre-lithiated negative electrode plate. The second pre-lithiated negative electrode plate of the present application has good environmental stability. When applied to a secondary battery, it can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. It can also simplify the preparation process of the secondary battery, improve production efficiency, and reduce preparation costs.

[0083] The pre-lithiated negative electrode sheet of the present application includes a negative electrode material layer, and the negative electrode material layer includes a negative electrode active material. The present application has no particular restrictions on the type of negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.

[0084] In the present application, the negative electrode material layer also includes a negative electrode binder and a negative electrode conductor. The present application does not particularly limit the type of negative electrode binder, as long as the purpose of the present application can be achieved, for example, the negative electrode binder may include but is not limited to polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, lithium polyacrylate, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. At least one of the negative electrode conductors is not particularly limited in the present application, as long as the purpose of the present application can be achieved, for example, the negative electrode conductor may include but is not limited to conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the negative electrode binder and the negative electrode conductive agent in the negative electrode material layer. Those skilled in the art may select according to actual needs as long as the purpose of the present application can be achieved.

[0085] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector (such as a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.), etc.

[0086] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector can be 4 μm to 20 μm. The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer can be 30 μm to 250 μm.

[0087] The third aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. The pre-lithiated negative electrode plate refers to the second pre-lithiated negative electrode plate. The secondary battery of the present application has a higher first coulombic efficiency, lower cycle capacity attenuation and higher energy density.

[0088] In the present application, the secondary battery also includes a positive electrode plate. The positive electrode plate includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its own thickness direction, or on two surfaces of the positive current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the positive current collector or a partial area of ​​the positive current collector. This application is not particularly limited as long as the purpose of this application can be achieved.

[0089] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0090] The positive electrode material layer of the present application includes a positive electrode active material, and the positive electrode active material includes a substance that can reversibly embed and extract active ions such as lithium ions. The positive electrode material layer can be one layer or more layers, and each layer in the multi-layer positive electrode material layer can contain the same or different positive electrode active materials. The present application has no special restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of the above-mentioned lithium nickel cobalt manganese oxide may include LiNi 0.95 Co 0.03 Mn 0.02 O2(Ni95),LiNi 0.91 Co 0.03 Mn 0.06 O2(Ni91), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3At least one of O2 (NCM111). The positive electrode material layer of the present application also includes a positive electrode conductor and a positive electrode binder. The present application has no special restrictions on the positive electrode conductor and the positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor in the positive electrode material layer may include at least one of the above-mentioned negative electrode conductors; the positive electrode binder in the positive electrode material layer may include at least one of the above-mentioned negative electrode binders. The present application has no special restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0091] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector can be 6 μm to 25 μm. The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided positive electrode material layer can be 25 μm to 250 μm.

[0092] In the present application, the secondary battery also includes an electrolyte. The electrolyte in the secondary battery may be the same as or different from the electrolyte pre-impregnated with the isolation membrane in the lithium-supplementing composite layer. The electrolyte in the secondary battery includes a lithium salt. The present application has no particular restrictions on the type of lithium salt, and lithium salts known in the art may be used. For example, the lithium salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2, LiTFSI), lithium bis(fluorosulfonyl)imide (Li(N(SO2F)2), LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiB(C2O4)2, LiBOB) or lithium difluorooxalatoborate (LiBF2(C2O4), LiDFOB). The present application has no particular restrictions on the mass percentage of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The electrolyte in the secondary battery also includes a non-aqueous organic solvent. The present application has no particular restrictions on non-aqueous organic solvents, as long as the purpose of the present application can be achieved. For example, the non-aqueous organic solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), vinylene carbonate, propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran.The above-mentioned other organic solvents may include, but are not limited to, at least one of 1,3-propane sultone, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester. The present application has no particular limitation on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0093] In the present application, the secondary battery also includes a separator. The separator is used to separate the positive electrode plate and the pre-lithiated negative electrode plate, prevent internal short circuits in the secondary battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The separator in the secondary battery can be the same as or different from the separator in the lithium supplement composite layer. The present application has no special restrictions on the separator in the secondary battery, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0094] In the present application, the separator may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder for the separator, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned separator binder, for example, it may be at least one of the aforementioned negative electrode binders. The polymer layer contains polymers, and the polymer material may include but is not limited to at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer.

[0095] The secondary battery of the present application also includes a packaging bag for containing a positive electrode plate, a separator, a pre-lithiated negative electrode plate and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0096] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0097] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator, the pre-lithiated negative electrode sheet, and the separator in order, and winding, folding, and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator, the pre-lithiated negative electrode sheet, and the separator in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0098] The fourth aspect of the present application provides an electronic device, which comprises the secondary battery in any of the above embodiments. The electronic device of the present application has a long service life and good performance.

[0099] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0100] Example

[0101] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0102] Test methods and equipment:

[0103] Electrolyte surface density test on the separator pre-impregnated with electrolyte

[0104] Before the separator is immersed in the electrolyte, weigh the mass of the separator, recorded as M1 g, and measure the area of ​​the separator, recorded as S mm 2 After the separator is soaked in electrolyte, the mass of the separator is weighed and recorded as M2 g. The surface density of the electrolyte on the separator pre-soaked in electrolyte (g / mm 2 )=(M2-M1) / S.

[0105] Lithium fluoride coverage test on the negative electrode surface

[0106] Take the first pre-lithiated negative electrode sheet, clean it with dimethyl carbonate (DMC) solvent in an argon atmosphere, and dry it, and cut a sample of 10mm×10mm and stick it on the sample stage. Use a scanning electron microscope (SEM) to obtain the morphological image of the surface of the negative electrode sheet, and adjust the acceleration voltage and working distance of the SEM to obtain a clear image. Based on the SEM image, energy dispersive X-ray spectroscopy (EDS) is used for elemental analysis. The presence of lithium fluoride is confirmed by detecting the characteristic X-ray peak of the fluorine element. The surface of the sample perpendicular to the thickness direction is scanned to obtain the distribution information of the fluorine element, that is, lithium fluoride on the surface of the negative electrode sheet. The distribution area of ​​lithium fluoride on the surface of the negative electrode sheet is obtained according to the distribution information. The ratio of the distribution area of ​​lithium fluoride to the surface area of ​​the negative electrode sheet sample perpendicular to the thickness direction is the coverage of lithium fluoride on the surface of the first pre-lithiated negative electrode sheet. The coverage of lithium fluoride on the surface of the second pre-lithiated negative electrode sheet is tested by the same test method as above.

[0107] Test of the mass content of hydrogen fluoride on the surface of negative electrode

[0108] Remove loose particles and free liquid from the surface of the first pre-lithiated negative electrode plate to keep the surface of the negative electrode material layer clean. Place the first pre-lithiated negative electrode plate in the detection window of the reflection Fourier transform infrared spectroscopy (FTIR) instrument, and use the attenuated total reflection accessory to improve the sensitivity of the test. Scan the first pre-lithiated negative electrode plate to obtain a reflection infrared spectrum. Find the characteristic peak of hydrogen fluoride in the infrared spectrum, which is usually at 3000cm -1 Up to 4000cm -1The infrared spectrum is compared with a standard spectrum with a known hydrogen fluoride content to calculate the mass content of hydrogen fluoride on the surface of the first pre-lithiated negative electrode. The mass content of hydrogen fluoride on the surface of the second pre-lithiated negative electrode is obtained by the same test method as above.

[0109] The first coulomb efficiency E1 and the second coulomb efficiency E2 test

[0110] A negative electrode sheet including a negative electrode current collector and a negative electrode material layer is provided, and a discharge treatment is performed on the negative electrode sheet according to the lithium replenishment method of the present application. After the discharge treatment is completed, the lithium replenishment composite layer is peeled off from the negative electrode sheet to obtain a first pre-lithiated negative electrode sheet. The first pre-lithiated negative electrode sheet is subjected to storage treatment to obtain a second pre-lithiated negative electrode sheet.

[0111] The design voltage range of the lithium-ion battery shall prevail. For example, when the design voltage range of the lithium-ion battery is 3.0V to 4.45V, the charge cut-off voltage is 4.45V and the discharge cut-off voltage is 3.0V.

[0112] The specific test steps are: prepare the lithium-ion battery by the first pre-lithiation negative electrode plate and the second pre-lithiation negative electrode plate, and test the first coulomb efficiency of the lithium-ion battery by the following method: charge the lithium-ion battery at 0.2C constant current to a cut-off voltage of 4.45V at 25°C, then charge at a constant voltage of 4.45V until the current is less than 0.05C, stand for 5 minutes, and then discharge at 0.2C constant current to a cut-off voltage of 3.0V. The capacity of the above charging process is recorded as C0, and the capacity of the above discharging process is recorded as C1. The first coulomb efficiency of the lithium-ion battery is calculated according to the following formula: first coulomb efficiency (%) = C1 / C0×100%. The first coulomb efficiency of the first pre-lithiation negative electrode plate applied to the lithium-ion battery is the first first coulomb efficiency E1, and the first coulomb efficiency of the second pre-lithiation negative electrode plate applied to the lithium-ion battery is the second first coulomb efficiency E2.

[0113] Cyclic performance test

[0114] The voltage range shall be based on the voltage range marked on the outer packaging of the lithium-ion battery. For example, when the voltage range marked on the lithium-ion battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V.

[0115] The specific test steps are as follows: at 25°C, the lithium-ion battery is charged and discharged for the first time, charged at a constant current of 0.2C to a cut-off voltage of 4.45V, then charged at a constant voltage of 4.45V until the current is less than 0.05C, and after standing for 5 minutes, discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, and the discharge capacity of the lithium-ion battery is measured to be A. Then, 400 charging and discharging cycles are performed according to the above steps in an environment of 25°C, and the discharge capacity of the lithium-ion battery at the 400th time is measured to be B. The cycle capacity retention rate of the lithium-ion battery is calculated according to the following formula: Cycle capacity retention rate (%) = B / A × 100%. The larger the value of the cycle capacity retention rate obtained by the test, the better the cycle performance of the lithium-ion battery and the smaller the cycle capacity attenuation.

[0116] Energy density test

[0117] The voltage range shall be based on the voltage range marked on the outer packaging of the lithium-ion battery. For example, when the voltage range marked on the lithium-ion battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V.

[0118] The specific test steps are: at 25℃, charge the lithium-ion battery at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, let it stand for 5 minutes, then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V, and let it stand for 5 minutes. The energy of the above discharge process is recorded as the discharge energy E. Calculate the volume V (mm) of the lithium-ion battery 3 ) = length × width × height. The energy density of lithium-ion batteries is calculated according to the following formula: Energy density (Wh / L) = E / V × 10 6 .

[0119] Example 1-1

[0120] <Preparation of pre-lithiated negative electrode sheet>

[0121] (1) A negative electrode active material silicon-carbon material (a composite material of silicon and carbon, based on the mass of the silicon-carbon material, the mass percentage of silicon element is 50%, and the mass percentage of carbon element is 50%), a negative electrode conductive agent acetylene black, a negative electrode binder styrene-butadiene rubber (SBR), and a negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 85:5:5:5, and deionized water is added as a solvent, and the mixture is stirred and mixed to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 28wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 90°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. The above steps are repeated on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Drying is carried out under vacuum conditions at 90°C for 1h, and then cold pressing, cutting, slitting, and welding of the pole ears are performed to obtain a negative electrode sheet with a specification of 80mm×1000mm. The single-sided coating density of the negative electrode material layer is 2.3 mg / cm 2 The single-sided thickness of the negative electrode material layer is 23 μm.

[0122] (2) Under the conditions of ambient temperature of 25° C. and humidity of 1.0%, the lithium foil was rolled into a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer. The roller pressure was 1.5 T / 10 mm, and the thickness of the lithium supplement layer was 15 μm, thereby obtaining a lithium supplement layer / support layer composite structure.

[0123] In an argon atmosphere glove box with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) and non-fluorine additive lithium hexamethyldisilazide were added and mixed evenly to obtain an electrolyte. The mass percentages of lithium salt, non-fluorine additive, fluorine-containing additive, and non-aqueous organic solvent based on the mass of the electrolyte are shown in Table 2.

[0124] A porous polypropylene film with a thickness of 5 μm (provided by Celgard) was placed in the above-prepared electrolyte, and was taken out after absorbing part of the electrolyte to obtain a separator pre-impregnated with electrolyte, and the surface density is shown in Table 3. The separator pre-impregnated with electrolyte was placed on the surface of the lithium replenishing layer to obtain a lithium replenishing composite layer.

[0125] (3) The lithium-replenishing composite layer and the negative electrode sheet are laminated so that the separator pre-impregnated with the electrolyte contacts the negative electrode material layer, and the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode sheet is shown in Table 3. The lithium-replenishing composite layer and the negative electrode sheet are subjected to discharge treatment, the positive electrode of the voltage control system is connected to the negative electrode sheet, and the negative electrode of the voltage control system is connected to the lithium-replenishing layer. The discharge treatment is divided into a first stage, a second stage, and a third stage in chronological order, wherein the constant current discharge current and discharge time of the first stage, the constant current discharge current and discharge time of the second stage, the constant current discharge current and discharge time of the third stage, and the temperature of the discharge treatment are shown in Table 1.

[0126] (4) After the discharge treatment is completed, the lithium supplement composite layer is peeled off from the negative electrode plate to obtain a first pre-lithiated negative electrode plate.

[0127] (5) The first pre-lithiated negative electrode sheet is subjected to storage treatment, and the temperature, humidity and time of the storage treatment are shown in Table 1, thereby obtaining a second pre-lithiated negative electrode sheet.

[0128] <Preparation of positive electrode sheet>

[0129] The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 110°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 110°C for 1h, and then after cold pressing, cutting, slitting, and welding the pole ears, a positive electrode sheet with a specification of 77mm×995mm is obtained. Among them, the single-sided coating surface density of the positive electrode material layer is 19.0mg / cm 2 The compaction density of the cold pressing process is 4.15g / cm 3 .

[0130] <Preparation of Electrolyte>

[0131] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) were mixed at a weight ratio of 3:1:3:3 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 was 12.5%, and the remainder was the base solvent.

[0132] <Preparation of Separator Film>

[0133] A porous polypropylene film with a thickness of 5 μm (provided by Celgard Company) was used as the isolation membrane.

[0134] <Preparation of lithium-ion batteries>

[0135] The prepared positive electrode sheet, separator, second pre-lithiated negative electrode sheet, and separator are stacked in order, so that the separator is between the positive electrode sheet and the second pre-lithiated negative electrode sheet to play an isolating role, and the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film packaging bag, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and an electrolyte is injected. After vacuum packaging, standing, degassing, trimming, and capacity processing steps, a lithium-ion battery is obtained.

[0136] Example 1-2 to Example 1-21

[0137] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0138] Example 2-1 to Example 2-14

[0139] Except that the components and contents of the electrolyte in which the separator in the lithium-supplementing composite layer is immersed are adjusted according to Table 2 in the preparation of the pre-lithiated negative electrode sheet, the rest is the same as that of Example 1-1.

[0140] Example 3-1 to Example 3-6

[0141] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1. The surface density of the electrolyte on the separator pre-impregnated with the electrolyte is regulated by adjusting the amount of electrolyte dripped onto the separator surface or the immersion time of the separator in the electrolyte.

[0142] Comparative Example 1

[0143] Except that the following preparation method is adopted in <Preparation of pre-lithiated negative electrode plate>, and a formation step (charging to 3.5V at a constant current of 0.02C, and then charging to 3.9V at a constant current of 0.1C) is added in <Preparation of lithium-ion battery>, the rest is the same as Example 1-1.

[0144] <Preparation of negative electrode sheet>

[0145] The negative electrode active material silicon carbon material (composite material of silicon and carbon, based on the mass of silicon carbon material, the mass percentage of silicon element is 50%, and the mass percentage of carbon element is 50%), the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder carboxymethyl cellulose lithium are mixed in a mass ratio of 85:5:5:5, and deionized water is added as a solvent, and the mixture is stirred and mixed to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 28wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 90°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Dry under vacuum conditions at 90°C for 1h, and then after cold pressing, cutting, slitting, and welding of the pole ears, a negative electrode sheet with a specification of 80mm×1000mm is obtained. The single-sided coating density of the negative electrode material layer is 2.3 mg / cm 2 The single-sided thickness of the negative electrode material layer is 23 μm.

[0146] Comparative Example 2

[0147] Except that the discharge treatment in <Preparation of Pre-lithiated Negative Electrode Sheet> only includes the first stage, and the constant current discharge current and discharge time of the first stage are shown in Table 1, the rest is the same as Example 1-1.

[0148] Comparative Examples 3 to 17

[0149] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0150] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.

[0151]

[0152]

[0153] From Examples 1-1 to 1-21 and Comparative Examples 1 to 17, it can be seen that the lithium supplementation method provided by the present application is used to prepare the second pre-lithiated negative electrode sheet and apply it to a lithium ion battery, and the lithium ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the present application can improve the first coulombic efficiency of the lithium ion battery, reduce the cycle capacity decay, and improve the energy density. However, the negative electrode sheet of Comparative Example 1 is not supplemented with lithium, the discharge treatment of the negative electrode sheet of Comparative Example 2 only includes the first stage, and any of the constant current discharge current and discharge time of the first stage, the second stage, and the third stage of the discharge treatment of the negative electrode sheet of Comparative Examples 3 to Comparative Examples 14 is not within the scope of the present application, and any of the temperature, humidity and time of the storage treatment of the negative electrode sheet of Comparative Examples 15 to Comparative Examples 17 is not within the scope of the present application. The lithium ion batteries of Comparative Examples 1 to Comparative Examples 17 cannot have a higher first coulombic efficiency, cycle capacity retention rate and energy density at the same time, indicating that it cannot simultaneously improve the first coulombic efficiency of the lithium ion battery, reduce the cycle capacity decay, and improve the energy density.

[0154] The constant current discharge current and discharge time of the first stage, the second stage, and the third stage usually affect the first coulombic efficiency, cycle capacity retention rate, and energy density of the lithium-ion battery. From Example 1-1 to Example 1-13, Comparative Example 3 to Comparative Example 14, it can be seen that when the constant current discharge current of the first stage, the second stage, and the third stage is too small, such as Comparative Example 3, Comparative Example 7, and Comparative Example 11, the first coulombic efficiency, cycle capacity retention rate, and energy density of the lithium-ion battery are lower; when the constant current discharge current of the first stage, the second stage, and the third stage is too large, such as Comparative Example 4, Comparative Example 8, and Comparative Example 12, the cycle capacity retention rate of the lithium-ion battery is lower. When the discharge time of the first stage, the second stage, and the third stage is too short, such as Comparative Example 5, Comparative Example 9, and Comparative Example 13, the first coulombic efficiency, cycle capacity retention rate, and energy density of the lithium-ion battery are lower; when the discharge time of the first stage, the second stage, and the third stage is too long, such as Comparative Example 6, Comparative Example 10, and Comparative Example 14, the cycle capacity retention rate of the lithium-ion battery is lower, indicating that it is not possible to simultaneously improve the first coulombic efficiency of the lithium-ion battery, reduce the cycle capacity decay, and improve the energy density. When the constant current discharge current and discharge time of the first stage, the second stage, and the third stage are within the scope of this application, the lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate, and energy density, indicating that this application can improve the first coulombic efficiency of the lithium-ion battery, reduce the cycle capacity decay, and improve the energy density.

[0155] The temperature, humidity and time of storage treatment usually affect the first coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Example 1-1, Example 1-14 to Example 1-19, and Comparative Example 15 to Comparative Example 17 that when the storage treatment temperature is too low, the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery are relatively high, but the cost of storage treatment of the negative electrode plate increases, and practical application is difficult; when the storage treatment temperature is too high, such as Comparative Example 15, the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery are lower. When the humidity of the storage treatment is too high, such as Comparative Example 16, the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery are lower. When the storage treatment time is too short, the initial coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery are low, but it is difficult to prepare a lithium-ion battery in a short time after the negative electrode plate is replenished with lithium, and industrial application is difficult; when the storage treatment time is too long, such as in Comparative Example 17, the initial coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery are lower, indicating that it is not possible to simultaneously improve the initial coulombic efficiency of the lithium-ion battery, reduce the cycle capacity decay, and increase the energy density. When the temperature, humidity and time of the storage treatment are within the scope of this application, the lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that this application can improve the initial coulombic efficiency of the lithium-ion battery, reduce the cycle capacity decay, and increase the energy density.

[0156] The temperature of the discharge treatment usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-1, 1-20 and 1-21 that when the temperature of the discharge treatment is within the range of this application, the lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that this application can improve the first coulombic efficiency of the lithium-ion battery, reduce the cycle capacity attenuation, and improve the energy density.

[0157]

[0158] The mass percentage of non-fluorine additives usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 2-1 to 2-5 that when the mass percentage of non-fluorine additives is within the range of this application, the lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that this application can improve the initial coulombic efficiency of lithium-ion batteries, reduce cycle capacity attenuation, and improve energy density.

[0159] The mass percentage of fluorine-containing additives usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 2-6 and 2-8 that when the mass percentage of fluorine-containing additives is within the range of this application, the lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that this application can improve the first coulombic efficiency of lithium-ion batteries, reduce cycle capacity attenuation, and improve energy density.

[0160] The mass percentage of ethylene carbonate usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 2-9 to 2-12 that when the mass percentage of ethylene carbonate is within the range of this application, the lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that this application can improve the initial coulombic efficiency of lithium-ion batteries, reduce cycle capacity attenuation, and improve energy density.

[0161] The types of non-fluorine additives and fluorine-containing additives usually affect the initial coulombic efficiency, cycle capacity retention rate and energy density of lithium-ion batteries. It can be seen from Examples 1-1, 2-13 and 2-14 that the lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density by selecting non-fluorine additives and fluorine-containing additives within the scope of the present application, indicating that the present application can improve the initial coulombic efficiency of lithium-ion batteries, reduce cycle capacity attenuation, and improve energy density.

[0162] Table 3

[0163]

[0164] The interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode piece usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Example 1-1, Example 3-1 to Example 3-2 that when the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode piece is within the range of this application, the lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that this application can improve the initial coulombic efficiency of the lithium-ion battery, reduce the cycle capacity attenuation, and improve the energy density.

[0165] The surface density of the electrolyte on the separator pre-impregnated with electrolyte usually affects the initial coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-1, 3-3 to 3-6 that when the surface density of the electrolyte on the separator pre-impregnated with electrolyte is within the scope of this application, the lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that this application can improve the initial coulombic efficiency of the lithium-ion battery, reduce the cycle capacity attenuation, and improve the energy density.

[0166] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0167] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0168] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for replenishing lithium of a negative electrode plate, comprising the following steps: Providing a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; Providing a lithium supplement composite layer, the lithium supplement composite layer comprising a support layer, a lithium supplement layer and a separator pre-impregnated with an electrolyte, the lithium supplement layer being arranged between the separator pre-impregnated with an electrolyte and the support layer; The lithium-replenishing composite layer and the negative electrode plate are laminated, so that the isolation film pre-impregnated with the electrolyte contacts the negative electrode material layer, and the lithium-replenishing composite layer and the negative electrode plate are subjected to a discharge treatment, wherein the discharge treatment is divided into a first stage, a second stage and a third stage in chronological order, wherein the constant current discharge current of the first stage is 0.1C to 0.3C, and the discharge time is 0.008h to 0.28h, the constant current discharge current of the second stage is 1C to 2C, and the discharge time is 0.032h to 0.30h, and the constant current discharge current of the third stage is 0.3C to 0.5C, and the discharge time is 0.027h to 0.058h; After the discharge treatment is completed, the lithium supplement composite layer is peeled off from the negative electrode plate to obtain a first pre-lithiated negative electrode plate; The first pre-lithiated negative electrode sheet is stored in an environment of 20° C. to 30° C. and humidity ≤1.7% for 12 h to 72 h to obtain a second pre-lithiated negative electrode sheet.

2. The lithium supplementation method according to claim 1, wherein: The first coulombic efficiency of the first pre-lithiated negative electrode plate applied to the secondary battery is the first first coulombic efficiency E1, and the first coulombic efficiency of the second pre-lithiated negative electrode plate applied to the secondary battery is the second first coulombic efficiency E2, 90%≤E2 / E1≤100%.

3. The lithium supplementation method according to claim 2, wherein: 90%≤E1≤120%。 4. The lithium supplementation method according to claim 1, wherein: The coverage of lithium fluoride on the surface of the first pre-lithiated negative electrode plate is 45% to 85%, and the coverage of lithium fluoride on the surface of the second pre-lithiated negative electrode plate is 45% to 95%.

5. The lithium supplementation method according to claim 1, wherein: The mass content of hydrogen fluoride on the surface of the first pre-lithiated negative electrode plate is 10 ppm to 450 ppm, and the mass content of hydrogen fluoride on the surface of the second pre-lithiated negative electrode plate is 10 ppm to 500 ppm.

6. The lithium supplementation method according to any one of claims 1 to 5, wherein: The electrolyte includes an additive, the additive includes a non-fluorine additive, and the non-fluorine additive includes at least one of lithium hexamethyldisilazide, lithium thiodicarbonate, or lithium bis(oxalatoborate); Based on the mass of the electrolyte, the mass percentage of the non-fluorine additive is 0.1% to 10%.

7. The lithium supplementation method according to any one of claims 1 to 5, wherein: The electrolyte includes an additive, wherein the additive includes a fluorine-containing additive, and the fluorine-containing additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium fluorosulfonyl(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium (trifluoromethyl)(nonafluorobutyl)sulfonylimide, or lithium 1,3-perfluoropropanedisulfonylimide; Based on the mass of the electrolyte, the mass percentage of the fluorine-containing additive is 0% to 5%.

8. The lithium supplementation method according to any one of claims 1 to 5, wherein: The electrolyte includes a non-aqueous organic solvent, and the non-aqueous organic solvent includes ethylene carbonate; Based on the mass of the electrolyte, the mass percentage of the ethylene carbonate is 32.5% to 91%.

9. The lithium supplementation method according to any one of claims 1 to 5, wherein: The temperature of the discharge treatment is 25°C to 90°C.

10. The lithium supplementation method according to any one of claims 1 to 5, wherein: The interface pressure per unit area between the lithium supplementing composite layer and the negative electrode plate is 0.1 MPa to 0.6 MPa.

11. The lithium supplementation method according to any one of claims 1 to 5, wherein: The surface density of the electrolyte on the separator of the pre-immersion electrolyte is 3g / mm 2 Up to 60g / mm 2 .

12. The lithium supplementation method according to claim 11, wherein: The surface density of the electrolyte on the separator of the pre-immersion electrolyte is 5g / mm 2 Up to 30g / mm 2 .

13. A pre-lithiated negative electrode sheet obtained by the lithium supplementation method according to any one of claims 1 to 12. 14 . A secondary battery comprising the pre-lithiated negative electrode sheet according to claim 13 . 15 . An electronic device comprising the secondary battery according to claim 14 .

Citation Information

Patent Citations

  • Lithium ion battery in-situ pre-lithiation method and lithium ion battery

    CN109671999A

  • Negative electrode lithium supplementing method, negative electrode lithium supplementing device, negative electrode and battery

    CN115642318A

  • Electrochemical device, electronic device and method for preparing negative pole piece

    CN116097472A

  • Method for manufacturing electrode, electrode manufactured thereby, and lithium secondary battery comprising same electrode

    WO2024242400A1